2021
DOI: 10.1021/acs.jpcc.0c11412
|View full text |Cite
|
Sign up to set email alerts
|

How Nitrogen Doping Affects Hydrogen Spillover on Carbon-Supported Pd Nanoparticles: New Insights from DFT

Abstract: The process of hydrogen spillover on metal nanoparticle decorated carbon surfaces has been discussed for many years due to its importance for heterogeneous catalysis and hydrogen storage. The present density functional theory (DFT) study supports recent experimental observations of the hydrogen spillover process. By use of model systems of carbon-supported palladium nanoparticles, the details of hydrogen spillover are investigated and the effects of nitrogen doping on such processes are elucidated. It is found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…[58][59][60][61] The Hspillover can contribute to the reactivity through reversibly stored surface H-species that participate to Pd active site regeneration via reverse spillover. [62] Hydrogen spillover has already been reported for noble metal catalysts supported on O-doped, [63] N-doped [64,65] and S-doped [51,66] carbon materials. According to the heteroatom doping, different types of surface groups have been reported to facilitate the H-spillover on Pd catalysts, such as N-quaternary atoms for N-doped materials [65] and quinone groups for O-doped ones.…”
Section: Chemcatchemmentioning
confidence: 94%
See 3 more Smart Citations
“…[58][59][60][61] The Hspillover can contribute to the reactivity through reversibly stored surface H-species that participate to Pd active site regeneration via reverse spillover. [62] Hydrogen spillover has already been reported for noble metal catalysts supported on O-doped, [63] N-doped [64,65] and S-doped [51,66] carbon materials. According to the heteroatom doping, different types of surface groups have been reported to facilitate the H-spillover on Pd catalysts, such as N-quaternary atoms for N-doped materials [65] and quinone groups for O-doped ones.…”
Section: Chemcatchemmentioning
confidence: 94%
“…[62] Hydrogen spillover has already been reported for noble metal catalysts supported on O-doped, [63] N-doped [64,65] and S-doped [51,66] carbon materials. According to the heteroatom doping, different types of surface groups have been reported to facilitate the H-spillover on Pd catalysts, such as N-quaternary atoms for N-doped materials [65] and quinone groups for O-doped ones. [67] Interestingly, it was also reported that water molecules, present as solvent during 4-NP reduction, significantly facilitate the H-spillover reaction on carbon supports by acting as shuttle/stabilizer for the Hspecies.…”
Section: Chemcatchemmentioning
confidence: 94%
See 2 more Smart Citations
“…Modifying carbonaceous structures by hetero-atoms, such as boron or nitrogen, before metal decoration, was suggested to enhance their catalytic effect in comparison to the unmodified ones [71,[79][80][81][82][83][84][85][86][87][88][89]. Previously, we tested platinum-decorated, ammonia-treated activated carbons for carbon dioxide and methane gas storage [90].…”
Section: Introductionmentioning
confidence: 99%